Neoglacial increase in high-magnitude glacial lake outburst flood frequency, upper Baker River, Chilean Patagonia (47°S). (15th November 2020) - Vandekerkhove, Elke; Bertrand, Sebastien; Mauquoy, Dmitri; McWethy, Dave; Reid, Brian; Stammen, Sarah; Saunders, Krystyna M.; Torrejón, Fernando
Abstract: Glacial Lake Outburst Floods (GLOFs) constitute a major threat in glacierized regions. Despite a recent increase in the size and number of glacial lakes worldwide, there is only limited evidence that climate change is affecting GLOF frequency. GLOFs are particularly common in the Baker River watershed (Patagonia, 47°S), where 21 GLOFs occurred between 2008 and 2017 due to the drainage of Cachet 2 Lake into the Colonia River, a tributary of the Baker River. During these GLOFs, the increased discharge from the Colonia River blocks the regular flow of the Baker River, resulting in the inundation of the Valle Grande floodplain, which is located approximately 4 km upstream of the confluence. To assess the possible relationship between GLOF frequency and climate variability, four sediment cores collected in the Valle Grande floodplain were analyzed. Their geophysical and sedimentological properties were examined, and radiocarbon-based age-depth models were constructed. All cores consist of dense, fine-grained, organic-poor material alternating with low-density organic-rich deposits. The percentage of lithogenic particles, which were most likely deposited during high-magnitude GLOFs, was used to reconstruct the flood history of the last 2.75 kyr. Results show increased flood activity between 2.57 and 2.17 cal kyr BP, and between 0.75 and 0 cal kyr BP. These two periods coincide with Neoglacial advances that are coeval with periods of lower temperature and increased precipitation. Our results suggest that GLOFs are not a new phenomenon in the region. Although rapid glacier retreat is likely responsible for high GLOF frequency in the 21 st century, high-magnitude GLOFs seem to occur more frequently when glaciers are larger and thicker. Highlights: A 2.75 kyr flood record was generated from Valle Grande floodplain sediments. Flooding most likely represents high-magnitude Glacial Lake Outburst Floods. First continuous GLOF record that extends beyond instrumental datasets. High-magnitude GLOFs were more frequent during Neoglaciations III and IV. High-magnitude GLOF frequency decreases as glaciers thin and retreat.